Economic egoism. True or false? (Economic and Political Thought, 2020)
The aim of the article is to analyse the economic aspects of the phenomenonconsidered. It is usually perceived in ethical and moral terms, andthe conclusions drawn are superficial, aimed at showing symptoms. However,the analysis undertaken in the article is an attempt to identify the efficientcauses. Everyone seems to acknowledge the obvious fact that accumulatingwealth is inseparable from human nature and market economy mechanisms.This results in huge socio-economic inequalities, which are widely criticized.This is even more the case when inequalities result from fraud and tax evasion.Although the owners of great fortunes try to pacify the unfriendly oreven hostile attitude towards them, including through charity, however, thisdoes not fundamentally address the rising gap between incomes at nationaland global level among various socio-professional categories. Another verytelling sign of economic egoism is the rise of protectionism in internationaltrade in recent years. Fuelled by economic nationalism, it disorganizes globalexchanges by breaking down supply chains, which are equally important forindividual economies and the global economy. If you add to this other phenomena,such as the coronavirus epidemic, which reinforce even further thenegative consequences of economic egoism, then we are faced with a gloomypicture of the future of the world economy. This should mobilize us evenmore in the fight against its negative manifestations.
Keywords: economic egoism, fiscal and financial egoism, commercial egoism, protectionism, economic nationalism